Effect of Blend Levels on Composite Bread Prepared From Anchote (Coccinia abyssinica) Starch and Wheat Flour - Etalema Desta Tulu; Ramesh Duraisamy; Belay Haile Kebede; Alemu Mekonnen Tura (International Journal of Food Science)
Blending wheat flour with anchote starch offers a valuable approach to reducing the antinutritional factors present in anchote. However, the use of anchote starch as a blending ingredient for wheat bread has not yet been investigated. This study addresses this gap by extracting and characterizing starch from anchote (Coccinia abyssinica) as a supplementary ingredient to wheat flour bread. Anchote samples were collected from the western Oromia Region in Ethiopia, and wheat samples were obtained from the Bishoftu research center. Wheat flour was combined with anchote starch at varying levels of 5%, 10%, 15%, and 20%. The study analyzed proximate composition, mineral content, antinutritional factors, and functional properties for both anchote starch and the composite flour. Results, processed through one-way ANOVA at a 5% significance level, showed that moisture, ash, protein, fat, fiber, carbohydrate, and gross energy contents in the composite flour ranged, respectively, from 9.17% to 9.73%, 1.71% to 1.99%, 3.35% to 4.87%, 3.05% to 3.85%, 1.33% to 3.67%, 79.71% to 82.4%, and 370.49–374.71 kcal. As the proportion of anchote starch increased, mineral contents of calcium, sodium, iron, and zinc rose, while potassium, magnesium, and manganese levels declined. Functionally, increasing anchote starch led to higher bulk density and swelling power, while water and oil absorption capacities decreased. Antinutritional elements such as phytate, cyanide, and tannin were reduced with higher anchote starch levels. Sensory evaluations indicated that bread acceptability improved with increased anchote starch, reaching optimal levels at 20%. Overall, anchote starch shows promise for enhancing the nutritional profile of food products, adding beneficial minerals and fiber.